Design and development of a monitoring station for the long-term investigation of dust pollution effects on the performance of PV panels - Ndapuka, Andreas Tangeni (Stellenbosch : Stellenbosch University, 2015)
Thesis (MEng)--Stellenbosch University, 2015.